Komunikasi Pembangunan dalam Perspektif Islam Menjaga Keseimbangan Antara Modernitas dan Nilai Tradisional - Novri Rivaldi Chandra Putra; Tubagus Rizki Hardianysah; Irham Ritonga3; Darul Arifin; Angga Prayudha; Zainun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Development communication has a strategic role in promoting sustainable social change, especially in Muslim societies. In an Islamic perspective, development communication serves not only as a tool for infrmation dissemination, but also as a means of maintaining harmony between modernity and traditional values. This article examines how development communication can be designed and implemented with Islamic principles in mind, as well as the challenges and opportunities faced in the era of globalization. This approach highlights the importance of balancing modern innovations with the Islamic roots of local culture and traditions.